A Submicellar Liquid Chromatographic Method for Quantitative Determination of Muscle Relaxant Drug Baclofen in Solubilized System - Malvia, Hitesh; Kumar, Ashok; Sharma, Pratibha; Mishra, Ritesh (Asian Journal of Chemistry, 2017)
A high performance liquid chromatography method, using micellar solution above the critical micellar concentration (CMC) has been developed and validated to quantify baclofen (a muscle relaxant drug) in active pharmaceutical ingredients and pharmaceutical formulations. Process optimization was done at various conditions such as different surfactants, surfactant concentration, pH of buffer solution, solvent composition, solvent selection and different HPLC columns. An isocratic HPLC mode, column temperature 35 °C, Intersil ODS-3 V 250 × 4.6, 5 μm column, 0.8 mL/min mobile phase flow rate and UV detection wavelength at 220 nm was used for the purpose. The method was validated as per International Conference on Harmonization (ICH) guidelines viz., specificity, linearity, range, inter and intra-day precision, accuracy (recovery) and robustness. Forced degradation conditions such as basic, acidic, oxidative, thermal degradation and photolytic are applied to prove the stability indicating nature of the proposed method.